Isolation of Fungi Associated to Corn Seeds and Detection of Aflatoxins - A. R. T. Sarhan; S. M. Abu - Tabigh (Journal of Madenat Alelem University College, 2010)
This research was done to isolate the fungi associated to corn seeds collected from different areas of Babylon Province and to detect the aflatoxins produced by fungi in media and in corn seeds. Results showed that seven species of seed borne fungi belong to six genera : Alternaria, Aspergillus, Fusarium, Penicillium, Rhizoctonia and Rhizopus. The genus Aspergillus was the most frequent, productivity of A.flavus and A.niger to the aflatoxins in liquid media and in corn seeds were examined. It was found that ability of the two species to produce the aflatoxins B1 and B2 at concentration ranged from 6.31 to 12.56 for B1 and from 0.33 to 1.73 nanogram / ml for B2 . This result was proofed by the presence of the two aflatoxins in the corn seeds infected by A.flavus and A.niger at concentrations ranged from 2.94 to 6.46 for B1 and from 0.32 to 0.77 nanograms / ml.